Development of Occupational-based-Context Worksheets of Geometric Sequences and Series for Senior High School Students (APPLICATION: Applied science in Learning Research, 2023)
Mathematics activities should not just be a procedural problem. It should be presented in context, especially real-life contexts that students often encounter. One of the contexts that many students encounter in their daily lives is occupational context. By completing contextual-mathematical-activities, students do not just solve problems procedurally, but they need to understand the underlying mathematical-concepts so that they are able to identify what is known and what is being asked correctly, so that students are able to determine the right steps and formulas to apply in solving problems. Therefore occupational-context is potential to be used in developing mathematical activities. One of them is in learning concept of Geometric Sequences and Series. The use of occupational-context could help students understand the use of mathematical concept so it can help students gain better understanding on the concept they learnt. Therefore in this study it is developed students’ worksheet (LKPD) based on occupational-context for concept of geometric sequences and series. Research method used is Research and Design (R & D), by applying ADDIE model, consist of analysis, design, development, implementation and evaluation stages. Result of this study shows that LKPD developed is valid and practical to be implemented in actual classroom. The implementation of the LKPD shows that LKPD is effective in helping students learn and understand the concept of geometric sequences and series. Furthermore, students give good responses for the use of LKPD. This is implied by the average percentage of students’ responses is 82.67%.